Impact of Access and Benefit Sharing implementation on biological control genetic resources - Peter G. Mason; Barbara I. P. Barratt; Fernando Mc Kay; Johannette N. Klapwijk; Luciana C. Silvestri; Martin Hill; Hariet L. Hinz; Andy Sheppard; Jacques Brodeur; Marcello Diniz Vitorino; Philip Weyl; Kim A. Hoelmer (BioControl, 2023)
The third objective of the Convention on Biological Diversity, the fair and equitable sharing of benefits arising out of the use of genetic resources was further developed when the Nagoya Protocol on Access and Benefit Sharing came into effect in 2014. Interpretation of how this agreement is being implemented is wide-ranging and there are implications for biological control. A survey of biological control workers indicated that while some countries have facilitated access to biological control genetic resources, requirements in other countries have impeded biological control implementation. There was consensus that benefits to provider countries should be in the form of supporting local research communities. There was also agreement that the free use and exchange of biological control genetic resources has provided benefits to the global community, including to both providers and recipients of the agents. It is recommended that consideration of the free use and exchange principal should be a key element of Access and Benefit Sharing measures for the future.

International agreement for the use and exchange of classical biological control genetic resources: a practical proposal - Peter G. Mason; Fernando Mc Kay; Luciana C. Silvestri; Martin Hill; Philip Weyl; Hariet L. Hinz; Jacques Brodeur; Marcelo Diniz Vitorino; Barbara I. P. Barratt (BioControl, 2023)
The Nagoya Protocol on Access and Benefit Sharing (ABS) was implemented to further develop the third objective of the Convention on Biological Diversity, the fair and equitable sharing of benefits arising out of the utilization of genetic resources. Interpretation of this agreement is wide-ranging and there is concern that if ABS measures are poorly implemented biological control and the resultant public good will be greatly impeded. The ethos of multilateral use and exchange of genetic resources used in classical biological control will be particularly affected. In the spirit of the fair and equitable sharing of benefits arising out of the utilization of genetic resources, we propose a simple practical solution in the form of an international agreement on the use and exchange of classical biological control genetic resources.